Cover Image. (13th June 2022) - Jeong, Ahrum; Choi, Jae Myung; Lee, Hyun‐Jae; Kim, Gee Yeong; Park, Jong‐Keuk; Kim, Won Mok; Kuk, Seungkuk; Wang, Zhen; Hwang, David J.; Yu, Hyeonggeun; Jeong, Jeung‐hyun
Abstract : The cover image is based on the Research Article Transparent back‐junction control in Cu(In, Ga)Se2 absorber for high‐efficiency, color‐neutral, and semitransparent solar module by Ahrum Jeong et al., https://doi.org/10.1002/pip.3520 .